PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE TWO STAY TWO STRAY TERHADAP PENINGKATAN KETERAMPILAN MENYIMAK PESERTA DIDIK PADA MATA PELAJARAN BAHASA INDONESIA - Asep Priatna; Imas Patmawati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2020)
This research was motivated by the lack of listening skills of students in Indonesian Language subjects. This study aims to determine the effect of the Two Stay Two Stray type of cooperative learning model on the improvement of students' listening skills in Indonesian. This research was conducted at SDN Rancasari in the 2020/2021 school year with a research sample of 22 grade IV students. This research method using quantitative methods with a pre-experimental research design. Researchers used pretest and posttest to determine the increase and effect of the Two Stay Two Stray type of cooperative learning model. The data collection techniques in this study were through tests, observation and documentation. The data analysis technique in this study uses the N-Gain calculation to measure the improvement of students' listening skills in Indonesian subjects and hypothesis testing (t-test) to determine the effect of the Two Saty Two Stray type of cooperative learning model on improving the listening skills of students in the eyes. Indonesian language lessons. The results showed that (1) there was an influence of the Two Saty Two Stray type of cooperative learning model on the listening skills of students in Indonesian subjects. This is evidenced by the results of the hypothesis test (t test) with a significance value of 0.000 <0.05. And from the results of observations of student activity shows that each meeting has changed as much as 5% with an average result of 72.50% with a good category (2) there is an increase in students' listening skills in Indonesian subjects with an average N-Gain score 0.55 with